APLIKASI MONITORING PEMBELAJARAN IQRO’ PADA SANTRI TK QUR’AN ASSYUKURIAH BERBASIS WEB DAN ANDROID - Tifani Intan Solihati; Reni Febriani; Raden Kania; Nur Hidayanti; Ramdani Budiman; Abdul Aziz (Jurnal Sistem Informasi dan Informatika (Simika), 2025)
This study explores the design and development of applications to monitor student learning at TKQ Assyukuriyah. This research was conducted to increase the efficiency and effectiveness of the teaching and learning process, which was previously carried out conventionally and faced several obstacles, including loss or damage to books, and the ineffectiveness of providing learning progress reports from schools to parents. The formulation of the research problem is how the application provides access to questions for students and makes it easy to record reports on the results of evaluations of learning progress using the iqro' and juz amma methods with safe data storage and how parents obtain information on learning progress. This research aims to provide easy access to questions for students, teachers record the results of evaluations of learning progress in reading using the iqro and juz'amma methods with secure data storage and make it easier for parents to obtain information on learning progress. Using the waterfall method for software development. The results of this research show that this application has succeeded in simplifying the process of recording monitoring of students' learning progress by storing data safely, reducing the time and energy of teachers in preparing questions, and making it easier to provide information on learning progress to parents. Keywords: Monitoring, Kindergarten-Qur'an, Learning, School, Waterfall.word